FINANCIAL RATIO ANALYSIS ON PT CISARUA MOUNTAIN DAIRY TBK (2020-2024) - Ari Masfufah; Featy Octaviany (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the financial condition of PT Cisarua Mountain Dairy Tbk during 20202024 through liquidity, solvency, and profitability ratio analysis. The research method used is descriptive quantitative with a horizontal analysis technique based on the company's financial statements. Data were collected through literature studies, including books, journals, articles, and financial reports. The results show that the company has a fairly good liquidity condition in meeting short-term obligations. In terms of solvency, the company is able to manage its debt stably and maintain its capital structure. Meanwhile, profitability indicates the company's ability to generate profit from its assets and equity. Overall, the company's financial condition during 2020-2024 shows fairly good and stable performance.